Hippocrates' woman : reading the female body in ancient Greece - King, Helen, 1957- (Routledge, 1998)
This text is a study of the origins of gynaecology, an exploration of how the interior workings of the female body were understood and the influence of Hippocrates' theories on the gynaecology of subsequent ages.